2021
DOI: 10.1142/s0217590820500782
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intelligence on Economic and Financial Crime: A Cross-Country Study

Abstract: The aim of this paper is to explore the relationship between intelligence and economic and financial crimes. For this purpose, we use a cross-sectional sample of 182 countries for the time span of 2012–2017. Our research provides empirical evidence on the existence of a significant impact of intelligence upon economic and financial crimes. When we analyze the entire sample, we find that intelligent people are more prone to comply with the law and thus increase the efficiency of implementing government policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…At the international level, states have not agreed to provide a unified definition for economic and financial crimes (Leţia, 2014). For instance, US Legal (2020) reveals that cybercrimes, tax evasion, robbery, selling of controlled substances and abuses of economic aid are all examples of financial crimes (Achim et al , 2021). Moreover, Gottschalk (2010) presented a systematic approach to classify financial crime into main categories; labelled as corruption, fraud, theft and manipulation; with 14 other sub-categories (includes kickbacks, bribery, extortion, embezzlement, identity fraud, mortgage fraud, occupational fraud, money laundering, cybercrime, bid-rigging and insider trading) under the main categories.…”
Section: Understanding the Landscape Of Financial Crimes During A Cov...mentioning
confidence: 99%
“…At the international level, states have not agreed to provide a unified definition for economic and financial crimes (Leţia, 2014). For instance, US Legal (2020) reveals that cybercrimes, tax evasion, robbery, selling of controlled substances and abuses of economic aid are all examples of financial crimes (Achim et al , 2021). Moreover, Gottschalk (2010) presented a systematic approach to classify financial crime into main categories; labelled as corruption, fraud, theft and manipulation; with 14 other sub-categories (includes kickbacks, bribery, extortion, embezzlement, identity fraud, mortgage fraud, occupational fraud, money laundering, cybercrime, bid-rigging and insider trading) under the main categories.…”
Section: Understanding the Landscape Of Financial Crimes During A Cov...mentioning
confidence: 99%
“…A number of interdisciplinary cross-country investigations have demonstrated that unlawful acts undertaken by an individual or group of people to extract financial gains, such as corruption and money laundering, are explained by national intelligence (see, e.g. Potrafke, 2012; Achim et al , 2020). The current study demonstrates that illicit trade too is explained by national intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Several different outcome variables have been associated with national average IQ such as corruption (Potrafke, 2012; Achim et al , 2020), economic growth (Ram, 2007), economic welfare (Hafer, 2017), earnings management practices (Loy, 2018), gender inequality (Salahodjaev and Azam, 2015), happiness (Stolarski et al , 2015), product sophistication (Lapatinas and Litina, 2019), quality of institutions (Kanyama, 2014) and shadow economy (Salahodjaev, 2015). This has led Lynn and Vanhanen (2012) to describe intelligence as being “a unifying construct for the social sciences.”…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a higher educational level determines a higher level of understanding and respecting the laws. This improved understanding is associated with a smaller economic and financial crime and the shadow economy [ 69 ]. [ 67 ] argues that human capital negatively affects emerging shadow activities.…”
Section: Literature Reviewmentioning
confidence: 99%